Tuberculosis transmission between foreign- and native-born populations in the EU/EEA: a systematic review - Sandgren, Andreas; Schepisi, Monica Sañé; Sotgiu, Giovanni; Huitric, Emma; Migliori, Giovanni Battista; Manissero, Davide; van der Werf, Marieke J; Girardi, Enrico (The European respiratory journal, 2014)
Tuberculosis (TB) control programmes of many low TB incidence countries of the European Union/European Economic Area (EU/EEA) perceive challenges in controlling TB due to high numbers of TB in migrants from high-incidence countries. To assess the extent of TB transmission from the foreign-born to the native-born population, we quantitatively investigated the dynamics of TB transmission between these populations in the EU/EEA, using published molecular epidemiological studies. We searched PubMed and EMBASE databases from 1990 to August 2012. We identified 15 studies performed during 1992-2007 covering 12,366 cases, of which median (range) 49.2% (17.7%-86.4%) were foreign-born. The proportion of clustered isolates ranged between 8.5% and 49.1% of the total number of TB cases genotyped and among these, foreign-born cases were equally or more likely to have unique isolates compared to native-born cases. One third of the clusters were "mixed", i.e. composed of foreign- and native-born cases, involving 0-34.2% of all genotyped cases. Cross-transmission among foreign and native populations was bidirectional, with wide differences across studies. This systematic review provides evidence that TB in a foreign-born population does not have a significant influence on TB in the native population in EU/EEA.